Risk Factors for Prognosis in Patients With Severely Decreased GFR - Evans, Marie; Grams, Morgan E.; Sang, Yingying; Astor, Brad C.; Blankestijn, Peter J.; Brunskill, Nigel J.; Collins, John F.; Kalra, Philip A.; Kovesdy, Csaba P.; Levin, Adeera; Mark, Patrick B.; Moranne, Olivier; et al. (Kidney International Reports, 2018)
Introduction: Patients with chronic kidney disease (CKD) and estimated glomerular filtration rate (eGFR) <30 ml/min per 1.73 m2 (corresponding to CKD stage G4+) comprise a minority of the overall CKD population but have the highest risk for adverse outcomes. Many CKD G4+ patients are older with multiple comorbidities, which may distort associations between risk factors and clinical outcomes. Methods: We undertook a meta-analysis of risk factors for kidney failure treated with kidney replacement therapy (KRT), cardiovascular disease (CVD) events, and death in participants with CKD G4+ from 28 cohorts (n = 185,024) across the world who were part of the CKD Prognosis Consortium. Results: In the fully adjusted meta-analysis, risk factors associated with KRT were time-varying CVD, male sex, black race, diabetes, lower eGFR, and higher albuminuria and systolic blood pressure. Age was associated with a lower risk of KRT (adjusted hazard ratio: 0.74; 95% confidence interval: 0.69-0.80) overall, and also in the subgroup of individuals younger than 65 years. The risk factors for CVD events included male sex, history of CVD, diabetes, lower eGFR, higher albuminuria, and the onset of KRT. Systolic blood pressure showed a U-shaped association with CVD events. Risk factors for mortality were similar to those for CVD events but also included smoking. Most risk factors had qualitatively consistent associations across cohorts. Conclusion: Traditional CVD risk factors are of prognostic value in individuals with an eGFR <30 ml/min per 1.73 m2, although the risk estimates vary for kidney and CVD outcomes. These results should encourage interventional studies on correcting risk factors in this high-risk population.
EVALuna2:215686